2005
DOI: 10.1088/0953-8984/17/23/004
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Monte Carlo studies of nanoporous carbon from TiC

Abstract: The structures of nanoporous carbon prepared by chlorination of TiC at five different temperatures (700–1100 °C) have been studied by means of reverse Monte Carlo modelling of neutron diffraction data S(q), 0.3 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 37 publications
6
46
0
Order By: Relevance
“…[40][41][42][43][44]. However, the interpretation of diffraction data from these highly disordered materials is not straightforward.…”
Section: Evidence For Fullerene-like Structures In Microporous Carbonsmentioning
confidence: 99%
“…[40][41][42][43][44]. However, the interpretation of diffraction data from these highly disordered materials is not straightforward.…”
Section: Evidence For Fullerene-like Structures In Microporous Carbonsmentioning
confidence: 99%
“…The pore structure can be further analyzed by small-angle scattering techniques like X-ray scattering (SAXS) or neutron scattering (SANS), which allows also probing closed pores. For titanium carbide-derived carbon (TiC-CDC), which is subject of this study, sorption isotherm analysis [16][17][18][19][20][21][22] and scattering [16,[23][24][25] results are discussed in literature, showing that TiC-CDC synthesized below 900 °C shows pore sizes in the range of carbon molecular sieves. Equilibrium CO 2 adsorption isotherms demonstrated that with TiC-CDC high CO 2 uptakes can be realized [26].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the knowledge gained from experiments, simulation methods have been widely developed to model and characterize the nanostructures of carbon [33][34][35][36][37][38][39][40][41]. There are mainly two types of modeling approaches to build structures of nanoporous carbon materials, namely reconstruction methods and mimetic methods.…”
Section: Introductionmentioning
confidence: 99%
“…By using build units of carbon at various scales, detailed information of carbon structures can be gained from atomic to mesoscopic level. For instance, Reverse Monte Carlo (RMC) methods were extensively employed to retrace the atomic structures of carbon by comparison with several experimental measurements [34][35][36][37]. Beside the basic material properties, e.g.…”
Section: Introductionmentioning
confidence: 99%